Importance-Performance (IPMA) Analysis of Loyalty in Indonesia Cellular Operator During COVID-19 Pandemic - Rachmawati, Indira (Jurnal Manajemen Teknologi, 2020)
Abstract. During the pandemic of Covid-19, customer loyalty becomes the crucial thing that needs to be concerned by cellular operators due to the internet usage is growing rapidly in the activities of work from home and study from home. In dealing with this, the company can find out from the user response regarding to their experience, satisfaction, switching barriers, and corporate image. User experience consists of functionality, social, monetary, trustworthiness, and perceived service quality. This research was conducted to 385 respondents of Indonesian cellular operators that was spread by internet survey. expert opinion was conducted before distributing questionnaires as many as 75 items with quota sampling technique. Based on Importance and Performance Matrix Analysis (IPMA) results, it was found that companies must concentrate first on trustworthiness, satisfaction, and corporate image. Then pay attention to monetary, switching barriers, and social. Variables that were considered low priority are functionality and perceived service quality, this is because the company's performance was very high compared to the level of importance of the user.Keywords: Corporate image, COVID-19, IPMA, loyalty, user experienceAbstrak. Saat pandemi Covid-19, loyalitas pelanggan menjadi hal krusial yang perlu diperhatikan oleh operator seluler karena penggunaan internet berkembang pesat dalam aktivitas bekerja dari rumah dan belajar dari rumah. Dalam menghadapi hal ini, perusahaan dapat mengetahui dari tanggapan pengguna mengenai pengalaman, kepuasan, peralihan hambatan, dan citra perusahaan mereka. Pengalaman pengguna terdiri dari fungsionalitas, sosial, moneter, kepercayaan, dan kualitas layanan yang dirasakan. Penelitian ini dilakukan terhadap 385 responden operator seluler Indonesia yang disebarkan melalui survei internet. Pendapat ahli dilakukan sebelum menyebarkan kuesioner sebanyak 75 item dengan teknik quota sampling. Berdasarkan hasil Importance and Performance Matrix Analysis (IPMA), ditemukan bahwa perusahaan harus berkonsentrasi terlebih dahulu pada kepercayaan, kepuasan, dan citra perusahaan. Kemudian perhatikan moneter, peralihan hambatan, dan sosial. Variabel yang dianggap prioritas rendah adalah fungsionalitas dan persepsi kualitas layanan, hal ini dikarenakan kinerja perusahaan sangat tinggi dibandingkan dengan tingkat kepentingan pengguna.Kata Kunci: Citra perusahaan, COVID-19, loyalitas, pengalaman pengguna